Integrated Management of the Thick-Skinned Rhinoplasty Patient - Cobo, Roxana; Camacho, Juan Gabrie; Orrego, Jorge (Facial Plastic Surgery, 2018)
Patients with thick skin are a challenge in facial plastic surgery. Rhinoplasty is still the most frequently performed facial plastic procedure worldwide and it becomes very difficult to obtain optimal consistent results in these patients. A systematic presurgical skin evaluation is performed dividing skin into type I–III depending on the elasticity, oiliness, presence of skin alterations, size of skin pores, and laxity. Depending on the skin type, presurgical, surgical, and postsurgical management of the epidermis and dermis is defined. Preconditioning and treating thick skin can improve postsurgical results and reduce postsurgical unwanted results.
Keywords: thick skin; rhinoplasty; skin evaluation; acne prone